Risk assessment of new sequencing information on genetically modified soybean event 40‐3‐2. (7th August 2017) - ,; Papadopoulou, Nikoletta; Ramon, Matthew; Waigmann, Elisabeth
Abstract: The GMO Panel has previously assessed genetically modified (GM) soybean 40‐3‐2 as a single event and as part of a two‐event stack, 305423 × 40‐3‐2. These soybean events were found to be as safe as their conventional counterparts and other appropriate comparators with respect to potential effects on human and animal health and the environment. On 4 April 2017, European Commission requested EFSA to analyse new nucleic acid sequencing and updated bioinformatics data for soybean event 40‐3‐2 and to indicate whether the conclusions of the GMO Panel on the previously assessed GM soybeans remain valid. The new sequencing data indicated that, the sequence of soybean event 40‐3‐2 as present in the stacked soybean 305423 × 40‐3‐2 contains an additional nucleotide in the 5′ flanking region of a 72 bp additional insert of CP4 EPSPS present in soybean 40‐3‐2. Re‐examination of the original sequencing data of the single soybean event 40‐3‐2 by the applicant, indicated that this additional nucleotide was already present in the original plant material used for the risk assessment of soybean event 40‐3‐2. Thus, with the exception of bioinformatics analyses, the studies performed for the risk assessment of the single event soybean 40‐3‐2 and the two‐event stack soybean 305423 × 40‐3‐2 remain valid. The updated bioinformatic analyses performed on the corrected sequence did not give rise to safety issues. Therefore, EFSA concludes, based on the information provided, that the original risk assessment of the soybean event 40‐3‐2 as a single and the stacked soybean 305423 × 40‐3‐2 remains valid. Abstract : This publication is linked to the following EFSA Journal article:http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.4967/full